Connected but Conflicted: Separating Incompatible Roles in Organizations - Worren, Nicolay; Pope, Shawn (Academy of Management Review, 2024)
A fundamental organization design principle is to group interdependent roles into the same sub-units to minimize coordination costs. However, observations in organizations, as well as theorizing in other sub-fields, such as corporate governance, indicate that interdependent roles sometimes perform conflicting functions, suggesting that they should be separated rather than integrated. Building on work in systems theory and axiomatic design theory, we discuss how to reconcile these two perspectives. Our key proposal is to distinguish between ends and means, or functions (e.g., goals or mandates) and structures (e.g., roles). This conceptualization makes it possible for two roles to be simultaneously interdependent in work processes yet conflicted in goals. Our framework leads to a modification of the traditional organization design principle of grouping based on interdependencies. It also suggests an alternative explanation for the division of labor within organizations: Organizations divide labor not only to capture gains from specialization, but also to avoid functional conflict.